2019
DOI: 10.22438/jeb/40/4/mrn-1002
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for morphological and physiological traits in RILs of spring wheat population of WH1021 × WH711

Abstract: To identify the quantitative trait loci (QTLs) associated with various morphological and physiological traits. A recombinant inbred line (RIL) population of wheat (Triticum aestivum L.) derived from cross of heat tolerant parent WH1021 with heat sensitive parent WH711 was used. For creation of heat stress delay in sowing (four weeks) was done in late sown from timely sown. Days to heading, days to maturity, plant height along with physiological traits viz. photosynthetic rate, transpiration rate, intrinsic wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
2
6
1
Order By: Relevance
“…As shown in Figure 4, a number of the QTLs identified in this study were co-located with some of the previously reported QTLs under heat stress conditions on chromosomes 1A, 2A, 2B, 5B, 7B, 1D, and 2D [36][37][38][39][40][41][42][43]. For instance, a number of STI-TKW QTLs were co-localized with previously identified QTLs for HSI-TGW (heat susceptibility index of thousand-grain weight) and TKW under heat and combined heat-drought on chromosomes 1A, 2B, and 2D.…”
Section: Qtl Identified In All Environmentssupporting
confidence: 78%
“…As shown in Figure 4, a number of the QTLs identified in this study were co-located with some of the previously reported QTLs under heat stress conditions on chromosomes 1A, 2A, 2B, 5B, 7B, 1D, and 2D [36][37][38][39][40][41][42][43]. For instance, a number of STI-TKW QTLs were co-localized with previously identified QTLs for HSI-TGW (heat susceptibility index of thousand-grain weight) and TKW under heat and combined heat-drought on chromosomes 1A, 2B, and 2D.…”
Section: Qtl Identified In All Environmentssupporting
confidence: 78%
“…As shown in Figure 4, a number of the QTLs identified in this study were co-located with some of the previously reported QTLs under heat stress conditions on chromosomes 1A, 2A, 2B, 5B, 7B, 1D, and 2D [23,24,37,[39][40][41][42][43]. For instance, a number of STI-TKW QTLs were co-localized with previously identified QTLs for HSI-TGW (heat susceptibility index of thousand-grain weight) and TKW under heat and combined heat-drought on chromosomes 1A, 2B, and 2D.…”
Section: Qtls Identified In All Environmentssupporting
confidence: 77%
“…At seedling stage, very little is known for MTAs associated with roots under heat stress in wheat. In HS, two QTNs were identified on chr2D for SL and SW at 29 Mb which are located in close proximity of 4 QTL identified by Sangwan et al (2019) on chr2D at 27.9 cM for days to heading, days to maturity and photosynthetic rate.…”
Section: Discussionmentioning
confidence: 97%